Mating system variation in neotropical black mangrove, Avicennia germinans, at three spatial scales towards an expanding northern distributional limit. (5th January 2021) - Kennedy, John Paul; Sammy, Joshua M.; Rowntree, Jennifer K.; Preziosi, Richard F.
Abstract: Climate-driven range expansion of ecosystem-defining foundation species can have wide-reaching ecological consequences. Expansion may also result in mating system changes in these foundation species because of the ecological characteristics of range margins, such as greater conspecific isolation and reduced pollinator availability. It is important to understand how mating systems may change during expansion due to their direct influence on intraspecific genetic and demographic dynamics. Here, we used 12 microsatellite loci to genotype progeny arrays of the neotropical black mangrove ( Avicennia germinans ) at six collection sites (n = 23 maternal trees; 1, 612 genotyped propagules) along a latitudinal gradient towards a northern distributional limit on the Atlantic coast of Florida, USA (27.56–30.01 o N), where mangroves have expanded into salt marsh over the past several decades. We assessed mating system variation at three spatial scales. First, at the species-distribution level, published outcrossing rates for tropical conspecifics were more than two times higher than those for subtropical Florida A. germinans, consistent with reductions in pollinator diversity and in mangrove abundance with latitude. Second, at the population level, Florida outcrossing rates did not systematically decline towards the northern range limit, but instead, a more open pollen-dispersal neighbourhood at the transition from mangrove to salt marsh dominance may elevate outcrossing until conspecific abundances become too low towards the range limit. Third, at the individual level, outcrossing increased as conspecific cover increased at the Florida range margin, consistent with density-dependent plastic shifts in mating system. These findings suggest that ecological structure influences the A. germinans mating system at varying spatial scales. Further research needs to evaluate the effect of A. germinans mating system variation on the survival and fitness of offspring and on the extent of population-level local adaptation at expanding distributional limits.